Outcome of Endoscopic Cerebrospinal Fluid Rhinorrhoea Repair: An Institutional Study - Majhi, Sudhir (Indian J Otolaryngol Head Neck Surg, 2018)
Cerebrospinal fluid Rhinorrhoea is caused by an abnormal open communication between the subarachnoid space and the nasal cavity. The most common anatomic sites of such abnormal communication are found in the anterior skull base, namely, ethmoid roof, olfactory groove, roof of the sphenoid sinus and the posterior wall of the frontal sinus. It can be classified into traumatic or spontaneous. Spontaneous leaks are associated with highest recurrence rates following surgical repair. The repair of CSF Rhinorrhoea has rapidly evolved over the past 30 years. Prior to the advent of the endoscopic approach, craniotomy was used for repairs which carried a variable success rate and morbidity. The purpose of our study was to ascertain the outcome after Transnasal Endoscopic Repair of spontaneous CSF leaks. This was a prospective study conducted at the Department of ENT at Safdarjung Hospital, New Delhi between January 2015 and June 2016. The study comprised of eleven patients who presented with the complaint of watery nasal discharge and were diagnosed to have spontaneous CSF Rhinorrhoea. Proper clinical examination, nasal endoscopy and biochemical and cytological analysis of nasal secretions of the patient was done. High Resolution Computed Tomography and MRI scans of the nose and paranasal sinuses were done to identify precise location of CSF leak and the size of fistula. CT cisternography was done wherever required. Fistula was repaired via Transnasal endoscopic approach in a multi layered underlay fashion. Out of all eleven patients with spontaneous CSF leaks, most common site of leak was from left cribriform area. Four patients (36.36%) were found to have meningoencephalocele. No associated intracranial lesion was found and all patients did not have any benign intracranial hypertension. Our success rate of endoscopic repair on first attempt was 100% with recurrence in 1 patient after 4 months of repair. Endoscopic repair of CSF rhinorrhoea is safe and effective, with a very low complication rate. It has almost completely replaced the older open techniques. Accurate localization of leak site followed by multilayered closure of dural defect appear to be essential for successful endoscopic repair.